2010
DOI: 10.1159/000288313
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Knowledge, Attitude and Practice of Tehranian Adults and Their Relation to Serum Lipid and Lipoproteins: Tehran Lipid and Glucose Study

Abstract: Background/Aim: The high prevalence of non-communicable diseases and their risk factors among the general urban population of Tehran necessitates an urgent implementation of nutritional interventional programs to curtail these risk factors. This study aimed to provide preliminary data on the knowledge, attitude and practices of urban Tehranian adults regarding nutrition and their relation to major non-communicable disease risk factors and to assess the need for educational interventions. Methods: This cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 46 publications
5
22
3
1
Order By: Relevance
“…Although women in Tehran knew more about nutrition, had better attitudes towards nutrition and were significantly more likely to comply with dietary guidelines than men, nutritional practices in the family still followed men's preferences (Mirmiran et al . ). These findings from various countries and ours from Taiwan suggest that women prepare meals according to husbands’ preferences and needs, regardless of culture.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although women in Tehran knew more about nutrition, had better attitudes towards nutrition and were significantly more likely to comply with dietary guidelines than men, nutritional practices in the family still followed men's preferences (Mirmiran et al . ). These findings from various countries and ours from Taiwan suggest that women prepare meals according to husbands’ preferences and needs, regardless of culture.…”
Section: Discussionmentioning
confidence: 97%
“…Poorly educated individuals have poor nutritional outcomes because of difficulty reading and understanding written information, resulting in poor nutritional knowledge (Payette & Shatenstein , Mirmiran et al . , Aihara & Minai ). In Taiwan, older adults had little formal schooling as children; thus, 31% of older Taiwanese are illiterate and 92% with low literacy had never received dietary education/counselling (Chen et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results of the study on knowledge, attitude and practice of Tehranian adults about nutrition revealed that for knowledge 26.5, 52.7 and 20.8%, for attitude, 27.6, 48.9 and 23.5% and for practice, 27.4, 51.7 and 20.9% of individuals had desirable, moderate and weak knowledge scores. This study emphasized that age, gender and education are among the factors that can influence nutritional knowledge, attitude and practice [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Los resultados del presente estudio son similares a los obtenidos por Mirmiran y su equipo (30), quienes encontraron una relación directamente proporcional entre marcadores bioquímicos de síndrome metabólico (concentraciones séricas altas de colesterol LDL y nivel alto de triglicéridos) y el auto reporte de prácticas nutricionales saludables en una población de adultos en un entorno urbano. En este sentido, estudios relacionados con hábitos de alimentación han demostrado que los trabajadores de la salud pueden desempeñar un papel importante en ayudar a sus pacientes a adoptar y mantener comportamientos saludables (31).…”
Section: Discussionunclassified